2006
DOI: 10.1159/000093739
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Associates with Undermedication of Cardiovascular Diseases in the Elderly

Abstract: Objective: To compare medication use in patients suffering from cardiovascular disease with and without dementia. Subjects: All inhabitants aged 75 and older in Lieto, Finland (n = 462, participation rate 82%). Measurements: Direct standardised assessments of dementia and cardiovascular diseases. Quantification of drug use by self-report and by prescription and drug container checks. Results: In multivariate analyses, the odds ratio for demented cardiovascular patients receiving any cardiovascular medication (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
0
18
1
Order By: Relevance
“…Of the 13 articles three reported studies which were conducted in the USA [15,16], two each in the UK [17,18] and France [19,20] and one each in Brazil [21], Canada [22], Finland [23], Germany [24], Nigeria [25] and Norway [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 articles three reported studies which were conducted in the USA [15,16], two each in the UK [17,18] and France [19,20] and one each in Brazil [21], Canada [22], Finland [23], Germany [24], Nigeria [25] and Norway [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, AD-related cognitive impairments could increase mortality risk because they may hamper diagnosis and management of other diseases or increase the risk for accidents. 29,30 Increased mortality risk may also have resulted from AD pathology, which may compromise the physiological response to other illnesses. 31 However, in order to understand the relation between preclinical AD and mortality, further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Pokela et al reported a similar association between self-reported mobility and analgesic use in older persons [33]. Studies investigating differences in other medications between patients with and without dementia discussed further explanations for undertreatment: Löppönen et al found an undermedication for cardiovascular diseases in patients with dementia, especially a less frequent treatment with antithrombotic agents in stroke and beta-blockers in case of hypertension [34]. They forwarded that caution may be an explanation, as older subjects with dementia are known to have an increased risk of falls leading to trauma.…”
Section: Discussionmentioning
confidence: 99%